Barriers to hypertension and diabetes management in primary health care in Argentina: qualitative research based on a behavioral economics approach. Issue 3 (4th April 2019) - Belizan, Maria; Alonso, Juan P; Nejamis, Analía; Caporale, Joaquín; Copo, Mariano G; Sánchez, Mario; Rubinstein, Adolfo; Irazola, Vilma
Abstract: Despite efforts to improve detection and treatment of adults with hypertension and diabetes in Argentina, many public healthcare system users remain undiagnosed or face barriers in managing these diseases. The purpose of this study is to identify health system, provider, and user-related factors that may hinder detection and treatment of hypertension and diabetes using a traditional and behavioral economics approach. We did qualitative research using in-depth semistructured interviews and focus groups with healthcare providers and adult users of Public Primary Care Clinics. Health system barriers included inadequate care accessibility; poor integration between primary care clinics and local hospitals; lack of resources; and gender bias and neglect of adult chronic disease. Healthcare provider–related barriers were inadequate training; lack of availability or reluctance to adopt Clinical Practice Guidelines; and lack of counseling prioritization. From a behavioral economics perspective, bottlenecks were related to inertia and a status quo, overconfidence, and optimism biases. User-related barriers for treatment adherence included lack of accurate information; resistance to adopt lifelong treatment; affordability; and medical advice mistrust. From a behavioral economics perspective, the most significant bottlenecks were overconfidence and optimism, limited attention, and present biases. Based on these findings, new interventions that aim to improve prevention and control of chronic conditions can be proposed. The study provides empirical evidence regarding the barriers and bottlenecks in managing chronic conditions in primary healthcare settings. Results may contribute to the design of behavioral interventions targeted towards healthcare provision for the affected population. Abstract : Patients with diabetes and hypertension face many challenges to controlling their chronic conditions in primary care settings.